(untitled) (World Bulletin of Public Health, 2022)
The examination was attended by 102 patients over the age of 45 who had compression fractures in chest and lumbar spine during 2012-2021 years in neurosurgery departments of Neurosurgery and vertebrology departments of the clinic of Andijan State Medical Institute, the Republican emergency ambulance scientific center Andijan branch, as well as the Republican specialized Neurosurgery scientific and practical Center spinal surgery departments